The relationship between clinical symptoms of oral lichen planus and quality of life related to oral health - Maryam Alsadat Hashemipour; Sahab Sheikhhoseini; Zahra Afshari; Amir Reza Gandjalikhan Nassab (BMC, 2024)
Abstract Introduction Oral Lichen Planus (OLP) is a chronic and relatively common mucocutaneous disease that often affects the oral mucosa. Although, OLP is generally not life-threatening, its consequences can significantly impact the quality of life in physical, psychological, and social aspects. Therefore, the aim of this research is to investigate the relationship between clinical symptoms of OLP and oral health-related quality of life in patients using the OHIP-14 (Oral Health Impact Profile-14) questionnaire. Materials and methods This descriptive-analytical study has a cross-sectional design, with case-control comparison. In this study, 56 individuals were examined as cases, and 68 individuals were included as controls. After recording demographic characteristics and clinical features by reviewing patients' records, the OHIP-14 questionnaire including clinical severity of lesions assessed using the Thongprasom scoring system, and pain assessed by the Visual Analog Scale (VAS) were completed. The ADD (Additive) and SC (Simple Count) methods were used for scoring, and data analysis was performed using the T-test, Mann-Whitney U test, Chi-Square, Spearman's Correlation Coefficient, and SPSS 24. Results Nearly all patients (50 individuals, 89.3%) reported having pain, although the average pain intensity was mostly mild. This disease has affected the quality of life in 82% of the patients (46 individuals). The patient group, in comparison to the control group, significantly expressed a lower quality of life in terms of functional limitations and physical disability. There was a statistically significant positive correlation between clinical symptoms of OLP, gender, location (palate), and clinical presentation type (erosive, reticular, and bullous) of OLP lesions with OHIP-14 scores, although the number or bilaterality of lesions and patient age did not have any significant correlation with pain or OHIP scores. Conclusion It appears that certain aspects of oral health-related quality of life decrease in patients with OLP, and that of the OLP patient group is significantly lower in terms of functional limitations and physical disability compared to the control group. Additionally, there was a significant correlation between clinical symptoms of OLP and pain as well as OHIP scores.